Evaluation of neonatal candidemia: Emergence of non- albicans candida - Ritu Vaish (Perspectives In Medical Research, 2018)
Introduction: Candidemia is the most common blood stream infections in neonates with high mortality and morbidity, which have increased in its incidence over the last two decades. Recent studies have detected a significant shift from Candida albicans towards non-albicans Candida (NAC) species. Objective: The main aim of this study is to evaluate and establish this increase in incidence of candidemia in neonates mainly caused by non albicans species which has completely different spectrum of antifungal susceptibility and disease pattern. Materials & Methods: This prospective study was conducted for a period of one year from June 2015 to May 2016. Blood samples were collected aseptically from the neonates suspected of septicaemia. Blood culture was performed by automated Bact/ Alert 3D system [Biomerieux]. The identification was based on Gram stain showing Gram positive budding yeast cells, cultural characteristics and performing Germ tube test, for preliminary speciation of candida species. All the isolates showing negative for germ tube test were presumptively put all together as Nonalbicans candida. Results: Total number of neonatal candidemia cases were 94 out of whom 66 were males and 28 were females. Number of neonates with albicans candidemia were 20 and with non albicans candidemia were 74. Conclusion: Neonatal candidemia is a potential health problem in our tertiary care health center which mainly covers the rural population. Especially the increasing cases of non albicans candida pose a serious threat and require strict control policies and proper prophylaxis to prevent the mortality and morbidity in the nenonates and infants